Functions of S-nitrosylation in plant hormone networks - París, Ramiro; Iglesias, María J.; Terrile, Maria C.; Casalongué, Claudia A. (Frontiers in Plant Science, 2013)
In plants, a wide frame of physiological processes is regulated in liaison by both, nitric oxide (NO) and hormones. Such overlapping roles raise the question of how is the cross-talk between NO and hormones to trigger common physiological responses. In general, NO has been largely accepted as a signaling molecule that works in different processes. Among the most relevant ways NO and the NO-derived reactive species can accomplish their biological functions it is worthy to mention post-translational protein modifications. In the last years, S-nitrosylation has been the most studied NO-dependent regulatory mechanism. Briefly, S-nitrosylation is a redox-based mechanism for cysteine residue modification and is being recognized as a ubiquitous regulatory reaction comparable to phosphorylation. Therefore, it is emerging as a crucial mechanism for the transduction of NO bioactivity in plants and animals. In this mini-review, we provide an overview on S-nitrosylation of target proteins related to hormone networks in plants.